Sibling and School Bullying Victimization and Its Relation With Children’s Subjective Well-Being in Indonesia: The Protective Role of Family and School Climate - Borualogo, Ihsana Sabriani (Journal of interpersonal violence, 2025)
Studies on the influence of family and school climates on the relationships between sibling and school bullying victimization and children’s subjective well-being (SWB) in Indonesia are still scarce. The aims of this study are to investigate family and school climates as protective factors for children from the negative consequences of bullying by siblings or other children in school on SWB. The study used the third-wave data of the Children’s Worlds survey that was collected in Indonesia in October 2017. Participants of the study were children aged 10 and 12 years old (N = 15,604; 49.8% girls, 50.2% boys, Mean age = 10.55; SD = 1.17). There are four questionnaires used in the study: five items measure bullying at home and at school, the Children’s Worlds Subjective Well-Being Scale, six items measure family climate, and four items measure school climate. Data were analyzed using R and the lavaan library for multilevel structural equation modeling, using full information maximum likelihood (FIML) for missing data and robust maximum likelihood (ML) estimation. Results showed that children who experienced bullying incidents, both at home by siblings and at school, predicted lower levels of SWB. School climate and family climate predicted higher levels of SWB. Results also showed that school bullying interacted significantly with school climate, while sibling bullying interacted significantly with family climate. Schools with students that reported more positive levels of family climate also reported higher levels of SWB. Students from public schools reported higher levels of SWB, which is unexpected.